CFOA-Based Fractional Order PIλDδ Controller - Tada Comedang (Electronics, 2017)
Conventional Current Feedback Operational Amplifier (CFOA) is not current controllable or not electronically controllable. It is thus of interest to add a current mirror into the CFOA in order to make it current controllable. This modification can be achieved by using Diamond Transistor (DT) instead of going through complicated IC fabrication process. This work applies the modified CFOA in fractional order proportional integral derivative (PIλDδ) controller. Both simulation and experimental results confirm that the modified CFOA is electronically controllable.